(untitled) (Theatrum historiae, 2014)
This article presents the First Palestinian uprising (First Intifada) by narrative stories as the principal research and interpretative methodology. The main question of this article is which role the Intifada played in an individual ́s life, and which importance individuals attach to it. This article broadens the issue of this historical event by the individual ́s perspective.